AB0083 Takayasu arteritis with bilateral renal artery stenosis in a 17-year-old girl. (1st June 2001) - Aksu, K; Keser, G; Inal, V; Memis, A; Oksel, F; Hizli, N; Kabasakal, Y; Gümüsdis, G; Doganavsargil, E
Abstract : Background: Takayasu arteritis, commonly seen in young women, is a large vessel vasculitis, primarily affecting aorta and its major branches. Hypertension frequently accompanies Takayasu arteritis and in approximately 75% of the cases it is due to renal artery involvement, causing stenosis. Hereby, we report a 17-year-old girl with Takayasu arteritis, having bilateral renal artery stenosis, with unilateral atrophic and afunctional kidney. This patient, who was diagnosed as Takayasu arteritis 3 years ago, with typical physical findings such as absent upper extremity peripheric pulses and classical angiographical findings involving arcus aorta and its major arteries, has been referred to our rheumatology department because of uncontrolled hypertension. Renal Doppler ultrasound studies and angiography revealed bilateral renal artery stenosis with atrophic right kidney. Successful angioplasty, followed by stent replacement corrected the stenosis in the left renal artery. However, the stenosis in the right renal artery involved a longer segment and angioplasty or stent replacement was not possible. From technical point of view, there was no way for surgical bypass for the stenosis in the right renal artery. Furthermore, no function was observed in the right kidney during renal scintigraphy. Nephrectomy of the right kidney was planned, but it was not accepted by the patient. Since the left renal artery stenosis was corrected, renovascular hypertension maintained by the right renal artery stenosis was treated successfully by captopril and the patient was closely monitored with respect to renal function tests. In conclusion, renal artery stenosis should always be kept in mind in Takayasu arteritis with hypertension. Objectives: Methods: Results: Conclusion: